2D Electron Gas and Oxygen Vacancy Induced High Oxygen Evolution Performances for Advanced Co3O4/CeO2 Nanohybrids. Issue 21 (8th April 2019) - Liu, Ying; Ma, Chao; Zhang, Qinghua; Wang, Wei; Pan, Pengfei; Gu, Lin; Xu, Dongdong; Bao, Jianchun; Dai, Zhihui
Abstract: The rational design of atomic‐scale interfaces in multiphase nanohybrids is an alluring and challenging approach to develop advanced electrocatalysts. Herein, through the selection of two different metal oxides with particular intrinsic features, advanced Co3 O4 /CeO2 nanohybrids (NHs) with CeO2 nanocubes anchored on Co3 O4 nanosheets are developed, which show not only high oxygen vacancy concentration but also remarkable 2D electron gas (2DEG) behavior with ≈0.79 ± 0.1 excess e − /u.c. on the Ce 3+ sites at the Co3 O4 –CeO2 interface. Such a 2DEG transport channel leads to a high carrier density of 3.8 × 10 14 cm −2 and good conductivity. Consequently, the Co3 O4 /CeO2 NHs demonstrate dramatically enhanced oxygen evolution reaction (OER) performances with a low overpotential of 270 mV at 10 mA cm −2 and a high turnover frequency of 0.25 s −1 when compared to those of pure Co3 O4 and CeO2 counterparts, outperforming commercial IrO2 and some recently reported representative OER catalysts. These results demonstrate the validity of tailoring the electrocatalytic properties of metal oxides by 2DEG engineering, offering a step forward in the design of advanced hybrid nanostructures. Abstract : A novel 2D electron gas (2DEG) behavior, which is realized by integrating CeO2 nanocubes into Co3 O4 nanosheets, is demonstrated, and the obtained Co3 O4 /CeO2 nanohybrids show high electrocatalytic oxygen evolution reaction (OER) performances due to the increased concentration of oxygen vacancies and 2DEG‐promoted high conductivity and electron mobility at the Co3 O4 –CeO2 interface.